Sodium-ion positive electrode material, preparation method thereof, sodium-ion battery and application thereof

CN121149222BActive Publication Date: 2026-10-27SHANGHAI PUNA ENERGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511685730.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-18
Publication Date
2026-10-27
Estimated Expiration
2045-11-18

AI Technical Summary

Technical Problem

虽然磷酸盐具有较好的空气稳定性,但其热膨胀系数与层状氧化物的匹配度较低,导致在体系或环境温度变化时面临着包覆层脱落的风险

Benefits of technology

[0023]与现有技术相比,本发明至少可实现如下有益效果之一:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121149222B_ABST
    Figure CN121149222B_ABST
Patent Text Reader

Abstract

The application discloses a sodium-ion positive electrode material and a preparation method thereof, a sodium-ion battery and application, and belongs to the sodium-ion battery field, and solves the problems of poor air stability of transition metal oxides, high surface residual alkali content, existence of interface side reactions between the transition metal and electrolyte, transition metal dissolution, stress accumulation during the charging and discharging process, and structural degradation and the like in the prior art. The positive electrode material is a boron / silicate-coated layered metal oxide with a core-shell structure, and a general formula is Na m TMO2@Na x M y (SiO n ) z (BO3) 1‑z ; TM is a 3d transition metal, M is at least one of a transition metal and / or an alkaline earth metal, wherein 0.5<=m<=1.2, 0 The positive electrode material has good air stability, low surface residual alkali content, good storage and processing performance, and the positive electrode material has few interface side reactions with electrolyte in the sodium-ion battery, and has less stress accumulation during the charging and discharging process, and good structural integrity, and has a long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery technology, and particularly relates to a sodium-ion cathode material and its preparation method, sodium-ion batteries and their applications. Background Technology

[0002] Lithium-ion batteries are widely favored for energy storage due to their high energy conversion efficiency, long cycle life, and high energy density. However, the scarcity and uneven distribution of lithium resources have led to continuously increasing costs, making it difficult to meet the demands of large-scale energy storage. Therefore, sodium-ion batteries, which operate on a similar principle to lithium-ion batteries, have attracted widespread attention due to their abundant resources and low cost, with the development of cathode materials for sodium-ion batteries becoming paramount. Currently, layered oxides as sodium-ion batteries offer advantages such as high energy density and low production cost; however, their interface instability causes their charging cutoff voltage to reach or exceed 4.3V (vs. Na). + The sodium content (Na) undergoes a significant irreversible phase transition. This phase transition during charging and discharging leads to stress accumulation, resulting in structural collapse and capacity decay. Simultaneously, residual sodium sources during sintering react with water and carbon dioxide in the air, affecting its air stability, thus reducing its processability and increasing production costs. Surface residual alkali also exacerbates the corrosion of fluid aluminum, severely impairing battery life. Furthermore, due to the open nature of the layered structure, hydrogen from water molecules in the air easily displaces sodium from the layered oxide. The difference in ionic radius and electronegativity between hydrogen and sodium can cause interlayer slippage or structural collapse, resulting in poor air stability.

[0003] The above problems are usually solved by coating methods, mainly solid-phase coating and liquid-phase coating in existing technologies. Solid-phase coating involves simply mixing the coating layer and layered metal oxide in a solid state. This method is economical, but the coating effect is not ideal. Liquid-phase coating involves stirring the layered material and the coating in a liquid, resulting in a more uniform coating. Traditional liquid-phase coating typically uses phosphates as the coating material. Although phosphates have good air stability, their coefficient of thermal expansion is poorly matched with that of layered oxides, leading to the risk of coating detachment when the system or ambient temperature changes. Furthermore, phosphates have a relatively low Young's modulus, resulting in weak mechanical protection. For cathode materials like layered oxides with large volume changes, it is difficult to suppress the potential crack generation and propagation during cycling, and their physical barrier against electrolyte corrosion is also limited.

[0004] Therefore, overcoming the aforementioned defects of phosphate as a coating layer has become an urgent problem to be solved. Summary of the Invention

[0005] Based on the above analysis, the present invention aims to provide a sodium-ion cathode material and its preparation method, sodium-ion battery and application, to solve at least one of the following technical problems: (1) In the prior art, phosphate as a coating layer has a low degree of matching between its thermal expansion coefficient and the layered oxide, which leads to the coating layer being easy to fall off when the ambient temperature changes; (2) The Young's modulus of phosphate is relatively low, resulting in a weak mechanical protection effect, making it difficult to suppress the generation and propagation of cracks in the layered metal oxide during the cycling process, and at the same time, its ability to block electrolyte corrosion is limited.

[0006] The objective of this invention is mainly achieved through the following technical solutions: The first aspect of this invention provides a sodium-ion cathode material, wherein the cathode material is a layered metal oxide coated with boron / silicate and having a core-shell structure, with the general formula Na. m TMO2@Na x M y (SiO n ) z (BO3) 1-z ; TM is a 3d transition metal, where M is selected from at least one of Fe, Mn, Co, Ni, Mg, Zn, Cu, and Ca, wherein 0.5 ≤ m ≤ 1.2, 0 < x < 4, 0.5 ≤ y < 2, and 0 < y < 2. <z<1,3≤n≤4。

[0007] Furthermore, the 3d transition metal is selected from at least one of Mn, Fe, Co, Ni, Cu, Ti, Cr and V.

[0008] Furthermore, the layered metal oxide is a P2 and / or O3 phase.

[0009] Furthermore, in the sodium ion cathode material, the mass fraction of the boron / silicate coating layer is 0.5~10%.

[0010] A second aspect of the present invention provides a method for preparing a sodium-ion cathode material, comprising: S1. In the presence of a solvent, the metal compound is mixed evenly with the boron-containing compound and the silicon-containing compound to obtain solution A; S2. Mix the layered metal oxide with liquid A to obtain a mixed solution, and then dry it to obtain a mixed powder. S3. The mixed powder is subjected to heat treatment to obtain sodium ion cathode material.

[0011] Further, in step S1, the metal compound is selected from transition metals and / or alkaline earth metal compounds.

[0012] Further, in step S1, the metal compound is selected from at least one of nitrates, carbonates, acetates, and sulfates containing at least one metal element selected from Fe, Mn, Co, Ni, Cu, and Zn.

[0013] Furthermore, the boron-containing compound is selected from at least one of boric acid, ammonium hydrogen borate, and sodium borate.

[0014] Furthermore, the silicon-containing compound is selected from at least one of orthosilicic acid, metasilicic acid, and sodium silicate.

[0015] Further, in step S1, the molar ratio of the total molar amount of the transition metal compound to the boron-containing compound and the silicon-containing compound is 0.5~2:1.

[0016] Furthermore, the solvent is selected from at least one of water, methanol, ethanol, and n-butanol.

[0017] Furthermore, the concentration of transition metal ions in solution A is 0.005~0.1 mol / L.

[0018] Furthermore, in step S2, the amount of layered metal oxide added is such that the solid content in the mixture is 5-80 wt%.

[0019] Furthermore, the drying conditions include: a drying temperature of 50~200℃ and a drying time of 5~20h.

[0020] Furthermore, in step S3, the conditions for the heat treatment include: a heat treatment temperature of 300~1200℃ and a heat treatment time of 1~10h.

[0021] A third aspect of the present invention provides a sodium-ion battery, comprising the sodium-ion cathode material described in the first aspect.

[0022] The fourth aspect of this invention provides an application of the sodium-ion battery described in the third aspect in the field of power transportation or energy storage.

[0023] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: (1) This invention uses boron / silicate with higher mechanical strength and more stable chemical properties as the coating layer, and the abundant sodium source on the surface of the layered metal oxide as the nucleation site. A dense polyanion coating layer is grown in situ on the surface of the layered metal oxide using the liquid phase coating method. At the same time, the sodium source on the surface of the layered metal oxide is consumed to reduce its alkalinity, reduce the corrosion of the current collector, and significantly improve the cycle stability and air stability of the sodium-ion battery.

[0024] (2) The boron / silicate coating used in this invention has a high Young's modulus (60~90 GPa) and lattice energy (B~O bond energy ≈515 kJ / mol, Si~O bond energy ≈460 kJ / mol), and its mechanical strength and chemical stability are far superior to those of traditional phosphate coatings (Young's modulus ≈10 GPa, P~O bond energy ≈360 kJ / mol). During the sodium ion insertion / extraction process, the boron / silicate coating can effectively suppress microcracks caused by volumetric strain, maintain the structural integrity of the particles, and thus improve their cycle stability. At the same time, the thermal expansion coefficient of boron / silicate can be controlled by the composition (3~20×10). -6 / K), which matches the thermal expansion coefficient of the coating layer with that of the base material, can avoid the risk of coating layer peeling off due to temperature changes, thereby significantly improving the cycle life of the battery. Specifically, it can still maintain 80% capacity after more than 3,000 cycles at 1C rate.

[0025] (3) In this invention, a chemically bonded heterogeneous interface is formed between the boron / silicate coating layer and the layered metal oxide core. The interface has high energy and strong bonding, which can effectively resist the volume change stress during cycling, prevent the coating layer from falling off, and overcome the defects of insufficient cycling stability caused by physical adsorption or weak van der Waals forces between phosphate and layered metal oxide.

[0026] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. The objects and other advantages of the invention may be realized and obtained by means of the structures particularly pointed out in the written description and the accompanying drawings. Attached Figure Description

[0027] Figure 1 The NaNi prepared in Example 1 of this invention 1 / 3 Fe 1 / 3 Mn 1 / 3 XRD pattern of O2@NaFeSiO4.

[0028] Figure 2 The NaNi prepared in Example 1 of this invention 1 / 3 Fe 1 / 3 Mn 1 / 3 SEM morphology of O2@NaFeSiO4.

[0029] Figure 3 The NaNi prepared in Example 1 of this invention 1 / 3 Fe 1 / 3 Mn 1 / 3 Charge-discharge curves of O2@NaFeSiO4 at a 0.1C rate.

[0030] Figure 4shows the capacity retention of the button cell prepared from the positive electrode material obtained in Example 1 of the present invention during cycling at 1C rate.

[0031] Figure 5 is a schematic diagram of the core-shell structure of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2@NaFeSiO4 prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] Hereinafter, the preferred embodiments of the present invention are specifically described, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to explain the principle of the present invention.

[0033] In a first aspect, the present invention provides a sodium-ion positive electrode material, which is a boron / silicate-coated layered metal oxide with a core-shell structure, with the general formula of Na m TMO2@Na x M y (SiO n ) z (BO3) 1-z ; TM is a 3d transition metal, M is selected from at least one of Fe, Mn, Co, Ni, Mg, Zn, Cu and Ca, wherein 0.5≤m≤1.2, 0<x<4, 0.5≤y<2, 0<z<1, 3≤n≤4, and in the coating layer, the molar ratio of borate calculated as boron to silicate calculated as silicon is 1:1-1.5.

[0034] In the present invention, the boron / silicate with higher mechanical strength and more stable chemical properties is used as the coating layer, which forms a chemically bonded heterogeneous interface with the layered metal oxide that provides high battery capacity, combining the high capacity of the layered metal oxide and the high stability of the boron / silicon oxygen-containing compound, solving the inherent interface instability problem of the layered metal oxide material, effectively resisting the volume change stress during cycling, avoiding the shedding of the coating layer, thereby significantly improving the cycle life and cycle stability of the battery. When the molar ratio of borate calculated as boron to silicate calculated as silicon in the coating layer is 1:1-1.5, a higher cycle life can be obtained.

[0035] According to some embodiments of the present invention, specifically, the 3d transition metal is selected from at least one of Mn, Fe, Co, Ni, Cu, Ti, Cr and V, which utilizes the unfilled d-electron orbitals of the 3d transition metal to provide a reversible redox reaction, laying a foundation for the high specific capacity of the sodium-ion battery positive electrode material.

[0036] According to some embodiments of the present invention, specifically, M is selected from at least one of Fe, Mn, Co, Ni, Mg, Zn, Cu, and Ca. On the one hand, this ensures that a firmly bonded heterogeneous interface can be formed between the coating layer and the layered metal oxide, preventing the coating layer from falling off. On the other hand, the above elements can construct a boron / silicate crystal structure with high Young's modulus and high thermal stability.

[0037] According to some embodiments of the present invention, and considering the selectivity of application scenarios, the layered metal oxide is specifically a P2 and / or O3 phase.

[0038] In this invention, by way of example, the layered metal oxide is selected from O3-type NaNi. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, O3 type NaNi 0.5 Mn 0.3 Co 0.2 O2 and P2 type Na 2 / 3 Ni 1 / 3 Mn 2 / 3 O2.

[0039] According to some embodiments of the present invention, in the sodium ion cathode material, the mass fraction of the boron / silicate coating layer is 0.5-10%.

[0040] In this invention, it should be noted that the mass fraction of the boron / silicate coating layer meets the above-mentioned range, which can effectively suppress the dissolution of transition metals and / or alkaline earth metals, thereby improving the cycle performance of sodium-ion batteries. The inventors have found that when the mass fraction of the coating layer is less than 0.5%, there are "bare islands" on the surface of the cathode material particles, and the electrolyte can still penetrate from the defects, affecting the cycle performance. On the other hand, when the mass fraction of the coating layer is greater than 10%, it will become an obstacle to ion diffusion and increase the cost.

[0041] For example, further, the mass fraction of the boron / silicate coating layer is 0.5%, 1%, 1.5%, 2%, 3%, 5%, 5.5%, 6%, 7%, 8%, 9%, 10%, and any two of the above values. Considering ensuring the formation of a continuous film on the particle surface and further improving the cycle performance of the battery, the mass fraction of the boron / silicate coating layer is 2 to 4%.

[0042] A second aspect of the present invention provides a method for preparing a sodium-ion cathode material, comprising: S1. In the presence of a solvent, the metal compound is mixed evenly with the boron-containing compound and the silicon-containing compound to obtain solution A; S2. Mix the layered metal oxide with liquid A to obtain a mixed solution, and then dry it to obtain a mixed powder. S3. The mixed powder is heat-treated to obtain a sodium ion cathode material; The molar ratio of boron-containing compounds (calculated as boron) to silicon-containing compounds (calculated as silicon) is 1:1-1.5.

[0043] In this invention, boron / silicate, which has more stable chemical properties, is used as the coating layer. The abundant sodium source on the surface of the layered metal oxide is used as the nucleation site. A dense polyanion membrane is grown in situ on the surface of the layered metal oxide using a liquid-phase coating method. This method is simple and low in cost. At the same time, the generated polyanion membrane can consume the sodium source on the surface of the layered metal oxide to reduce its alkalinity, reduce corrosion of the current collector, and significantly improve the cycle stability and air stability of the sodium-ion battery.

[0044] According to some embodiments of the present invention, taking into account the capacity of the cathode material, specifically, in step S1, the metal compound is selected from transition metals and / or alkaline earth metal compounds.

[0045] According to some embodiments of the present invention, in order to further improve the capacity of the cathode material and at the same time match the coating layer to improve cycle performance, specifically, in step S1, the metal compound is selected from at least one of nitrates, carbonates, acetates and sulfates containing at least one metal element selected from Fe, Mn, Co, Ni, Cu and Zn.

[0046] In this invention, the low-temperature decomposition products such as nitrates, acetates, and sulfates are gases with no residual carbon, which can avoid the disruption of transition metal valence states caused by carbon reduction, making the cathode material more stable and enabling a more uniform distribution of Si and / or B.

[0047] According to some embodiments of the present invention, the boron-containing compound is selected from at least one of boric acid, ammonium borate and sodium borate, and the silicon-containing compound is selected from at least one of orthosilicic acid, metasilicic acid and sodium silicate.

[0048] In this invention, the boron-containing compound and the silicon-containing compound are selected from the above-mentioned types. The hydroxide ions generated after hydrolysis can condense with the hydroxyl groups on the surface of the layered metal oxide to form chemical bonds rather than physical adsorption, thereby increasing the interfacial energy. At the same time, it can improve the electronic conductivity without increasing side reactions.

[0049] According to some embodiments of the present invention, in step S1, the molar ratio of the metal compound to the total molar amount of the boron-containing compound and the silicon-containing compound is 0.5 to 2:1, for example 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 2:1, preferably 0.8 to 1.2:1.

[0050] In this invention, the molar ratio of the metal compound to the total molar amounts of the boron-containing and silicon-containing compounds within the aforementioned range will lead to the generation of a large number of non-target impurities, thereby affecting battery capacity and cycle performance. Excessive metal oxides will result in excessively high ionic conductivity, exacerbating side reactions, while excessive free boron / silicates will block ion transport channels, increase interfacial impedance, and reduce battery specific capacity.

[0051] According to some embodiments of the present invention, specifically, the solvent is selected from at least one of water, methanol, ethanol and n-butanol.

[0052] According to some embodiments of the present invention, the concentration of transition metal ions in solution A is 0.005~0.1 mol / L. If the concentration of solution A is too low, it is not conducive to the uniform coating of ions on the surface of layered oxide materials, and the solvent evaporation process is more time-consuming and labor-intensive. If the concentration of solution A is too high, the metal ions may agglomerate and form nuclei, affecting the coating.

[0053] In this invention, by way of example, the concentration of transition metal ions in solution A is 0.005 mol / L, 0.008 mol / L, 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, or 0.05 mol / L, preferably 0.01 to 0.05 mol / L.

[0054] According to some embodiments of the present invention, considering that the layered metal oxide can be fully wetted without increasing drying energy consumption and cost due to excessive dilution, specifically, in step S2, the amount of layered metal oxide added is such that the solid content in the mixture is 5~80wt%, for example, it can be 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 20wt%, 25wt%, 30wt%, 40wt%, 50wt%, 60wt%, 80wt%, preferably 10~20wt%.

[0055] In this invention, it is understood that, before mixing the layered metal oxide with liquid A, it is preferable to calcine it at 750~1100℃ for 10~20h to ensure that the precursor reaction is sufficient to obtain highly crystalline layered oxide particles.

[0056] According to some embodiments of the present invention, considering that the layered metal oxide and borosilicate coating is more uniform, the drying conditions specifically include: a drying temperature of 50~200°C and a drying time of 5~20h.

[0057] According to some embodiments of the present invention, in step S3, the conditions of the heat treatment include: a heat treatment temperature of 300~1200℃ and a heat treatment time of 1~10h.

[0058] In this invention, a heat treatment temperature below 300°C will result in incomplete reaction; if it is above 1200°C, it will lead to the destruction of the layered metal oxide or coating structure and excessive grain growth, thereby reducing specific capacity and cycle performance.

[0059] In this invention, the method further includes crushing and sieving the heat-treated mixed powder. It is understood that the crushing process can be air jet milling, ball milling, etc., and the particle size of the powder after sieving is 1~100μm.

[0060] A third aspect of the present invention provides a sodium-ion battery, comprising the sodium-ion cathode material described in the first aspect of the present invention.

[0061] It is understood that the sodium-ion battery can be a button cell, a pouch cell, or a cylindrical cell, etc., the electrolyte is an ester or ether electrolyte, the negative electrode can be metallic sodium, carbon material, elemental metal, metal oxide, etc., and the separator can be polyethylene (PE), polypropylene (PP), or a solid electrolyte, etc.

[0062] It is understood that the sodium-ion battery can be prepared according to conventional methods in the art.

[0063] The fourth aspect of this invention provides an application of the sodium-ion battery described in the third aspect in the field of power transportation or energy storage.

[0064] In this invention, the sodium-ion battery retains a capacity of over 80% after 3000 cycles at 1C rate. When applied to electric vehicles, this ensures the lifespan of the power battery and can significantly reduce the cost of vehicle or battery replacement for users.

[0065] The sodium-ion battery retains over 95% of its capacity after 7 days of air exposure, and has low surface alkali residue (pH value not greater than 9.0). Its sensitivity to environmental humidity decreases during long-term operation, improving the reliability of the energy storage power station and reducing maintenance requirements.

[0066] The technical solution will be described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention.

[0067] In the following embodiments, the performance evaluation process of the cathode material in sodium-ion batteries is as follows: The cathode material, conductive agent (SuperP), and binder (polyvinylidene fluoride, PVDF) are mixed at a mass ratio of 94:3:3 and dispersed in N-methylpyrrolidone. The dispersion is coated onto aluminum foil and vacuum dried at 120°C for 12 hours. The electrode sheet is rolled under a pressure of 5 MPa and then cut into 12 mm diameter discs. A coin cell CR2016 battery is assembled in an argon-filled glove box. The cathode is the prepared electrode sheet, the anode is a 14 mm diameter sodium metal sheet, the electrolyte is 1 mol / L NaPF6 dissolved in ethylene carbonate and propylene carbonate at a volume ratio of 1:1, and the separator is glass fiber. The battery casing is made of 316 stainless steel. The material undergoes its first charge-discharge cycle at 0.1C, with a charging cut-off voltage of 4.3V and a discharging cut-off voltage of 1.5V. The test temperature is 25°C.

[0068] The specific capacity of the first charge cycle was tested according to the above process, and the value of the specific capacity of the 0.1C charge cycle was obtained. The reversible specific capacity of the first cycle was tested according to the above process to obtain the value of the 0.1C discharge specific capacity; Cycling performance was assessed by cycling the battery at 25°C and 1C rate until the capacity retention rate reached 80%, and recording the number of cycles.

[0069] Example 1 S1. Take 0.096g of orthosilicic acid and 0.404g of ferric nitrate nonahydrate (molar ratio of 1:1) and add them to 50mL of water. Stir thoroughly to form solution A. The concentration of transition metal ions is 0.02mol / L. S2. Take 7g of calcined NaNi (sintered at 800℃ for 12h under oxygen atmosphere). 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was added to solution A, and the solid content of the mixture was 12.2 wt%. After stirring for 30 min, the mixture was filtered and dried at 80 °C for 10 h. Then, it was placed in a muffle furnace and calcined at 600 °C for 2 h in air atmosphere to obtain NaNi with O3 phase uniformly coated by NaFeSiO4. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2. Testing revealed that the mass fraction of the silicate-based coating layer in the sodium-ion cathode material was 2.38%.

[0070] Example 2 S1. Take 0.062g of boric acid and 0.251g of manganese nitrate tetrahydrate (molar ratio of the two is 1:1) and add them to 40mL of water. Stir thoroughly to form solution A with a concentration of 0.025mol / L. S2, Take 5g of calcined NaNi 1 / 3 Fe 1 / 3 Mn1 / 3 O2 (sintering conditions as in Example 1) was added to solution A, the solid content of the mixture was 11.0 wt%, stirred for 30 min, filtered, and dried at 80 °C for 10 h. Then it was placed in a muffle furnace and calcined at 600 °C for 2 h in air atmosphere to obtain NaNi with O3 phase uniformly coated with NaMnBO3. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2. Testing revealed that the mass fraction of the borate coating layer in the sodium ion cathode material was 2.66%.

[0071] Example 3 S1. Take 0.048g of orthosilicic acid, 0.031g of boric acid and 0.291g of cobalt nitrate hexahydrate, wherein the molar ratio of silicate ions: borate ions: cobalt ions is 1:1:2, add them to 25mL of water, and stir thoroughly to form solution A. The concentration of transition metal ions is 0.04mol / L.

[0072] S2, Take 5g of calcined NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 (sintering conditions as in Example 1) was added to solution A, the solid content of the mixture was 16.5 wt%, and after stirring for 30 min, it was filtered and dried at 80°C for 10 h. The dried mixture was then calcined in a muffle furnace at 600°C for 2 h in air atmosphere to obtain Na. 1.5 Co(BO3) 0.5 (SiO4) 0.5 Coated O3 phase NaNi 1 / 3 Fe 1 / 3Mn 1 / 3 O2. Testing revealed that the boron / silicate coating layer in the sodium-ion cathode material comprised 3.27% by mass.

[0073] Example 4 S1. Take 0.0576g of orthosilicic acid, 0.0248g of boric acid, 0.1205g of manganese nitrate tetrahydrate and 0.1455g of cobalt nitrate hexahydrate, wherein the molar ratio of silicate ion: borate ion: manganese ion: cobalt ion is 6:4:5:5, add them to 40mL of water, and stir thoroughly to form solution A. The total concentration of transition metal ions is 0.025mol / L.

[0074] S2, Take 5g of calcined NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 (sintering conditions as in Example 1) was added to solution A, the solid content of the mixture was 11.0 wt%, and after stirring for 30 min, it was filtered and dried at 80°C for 10 h. The dried mixture was then calcined in a muffle furnace at 600°C for 2 h in air atmosphere to obtain uniform Na. 1.6 Co 0.5 Mn 0.5 (BO3) 0.4 (SiO4) 0.6 Coated O3 phase NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2. Testing revealed that the boron / silicate coating layer in the sodium-ion cathode material comprised 3.14% by mass.

[0075] Example 5 The method was followed in Example 1, except that 0.096 g of orthosilicic acid and 0.202 g of ferric nitrate nonahydrate were used, with a molar ratio of silicate to iron ions of 2:1. The final coating layer had a chemical composition of Na. 2.5 Fe 0.5 SiO4.

[0076] Example 6 The method is the same as in Example 1, except that 0.096g of orthosilicic acid and 0.404g of ferric nitrate nonahydrate are added to 200mL of water, and the concentration of transition metal ions in the resulting solution A is 0.005mol / L.

[0077] Example 7 The method was followed in Example 1, except that 0.048 g of orthosilicic acid and 0.202 g of ferric nitrate nonahydrate were used. Testing showed that the mass fraction of the coating layer in the sodium ion cathode material was 1.19%.

[0078] Example 8 The method is the same as in Example 1, except that 0.096g of orthosilicic acid and 0.291g of nickel nitrate hexahydrate are added in S1, wherein the molar ratio of silicate ions to nickel ions is 1:1. In S2, 5g of NaNi is added. 0.5 Mn 0.3 Co 0.2 O2. Finally, NaNi coated with Na2NiSiO4 is obtained. 0.5 Mn 0.3 Co 0.2 O2 material, coating layer mass fraction 2.38%.

[0079] Example 9 The method is the same as in Example 1, except that the layered metal oxide is P2 type Na. 2 / 3 Ni 1 / 3 Mn2 / 3 O2. Finally, NaFeSiO4-coated Na is obtained. 2 / 3 Ni 1 / 3 Mn 2 / 3 O2 material, coating layer mass fraction 2.38%.

[0080] Example 10 The method is the same as in Example 3, except that the dried mixture is calcined in a muffle furnace at 200°C for 2 hours in an air atmosphere.

[0081] Comparative Example 1 S1. Take 0.173g of ammonium dihydrogen phosphate and 0.404g of ferric nitrate nonahydrate and add them to 200mL of aqueous solution, and stir thoroughly to form solution A; S2, same as Example 1.

[0082] NaNi phase O3 coated with Na3Fe2(PO4)3 was obtained 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0083] Comparative Example 2 The method is the same as in Example 1, except that 0.0096g of orthosilicic acid and 0.0404g of ferric nitrate nonahydrate (molar ratio of 1:1) are added to 50mL of water and stirred thoroughly to form solution A, with a transition metal ion concentration of 0.002mol / L.

[0084] Comparative Example 3 The method is the same as in Example 1, except that NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The amount of O2 used is 70g. Testing revealed that the mass fraction of the silicate coating layer in the sodium ion cathode material is 0.24%.

[0085] Comparative Example 4 S1, 0.048g of orthosilicic acid, 0.031g of boric acid, and 0.291g of cobalt nitrate hexahydrate, wherein the molar ratio of silicate ions:borate ions:cobalt ions is 1:1:2, are added to 25mL of water and stirred thoroughly to form solution A. The concentration of transition metal ions is 0.04mol / L.

[0086] S2, Take 1g of calcined NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 (sintering conditions as in Example 1) was added to solution A, the solid content of the mixture was 3.79 wt%, and after stirring for 30 min, it was filtered and dried at 80°C for 10 h. The dried mixture was then calcined in a muffle furnace at 600°C for 2 h in air atmosphere to obtain Na. 1.5Co(BO3) 0.5 (SiO4) 0.5 Coated O3 phase NaNi 1 / 3 Fe 1 / 3Mn 1 / 3 O2. Testing revealed that the boron / silicate coating layer in the sodium-ion cathode material comprised 12.70% by mass.

[0087] Test case The positive electrode materials prepared in the examples and comparative examples were used to fabricate coin cells and their electrochemical performance was tested. The weight ratio of positive electrode material: conductive agent (SuperP): binder (PVDF) was 94:3:3; the negative electrode was a sodium metal sheet. The results are shown in Table 1.

[0088]

[0089] As can be seen from the above, this invention systematically improves the overall performance of sodium-ion cathode materials through boron / silicate coating, effectively reducing the surface residual alkali content of layered transition metal oxides, improving the thermal and air stability of the material, and significantly enhancing its reversible specific capacity and cycle stability as a sodium-ion battery cathode material. Specifically, all embodiments show significantly better results than the uncoated control: cycle life is greatly increased from 100 cycles to over 2000 cycles, air stability (capacity retention >90%) and thermal safety (exothermic onset temperature >295℃) are significantly enhanced, while surface residual alkali (pH ≤ 9.0) and interfacial impedance are significantly reduced.

[0090] Further embodiments within the preferred range exhibit superior performance, with a cycle life of up to 2900-3500 cycles and air stability exceeding 95.8%.

[0091] The cathode material prepared in Example 1 was further subjected to X-ray diffraction (XRD) testing, and the results are as follows: Figure 1 As shown in the figure, the crystal structure of the layered transition metal oxide is well maintained after the silica / borate coating, and the coating layer does not affect the crystallinity and the composition of the main phase.

[0092] Figure 2 This is a scanning electron microscope (SEM) image of the cathode material prepared in Example 1. It can be seen from the image that the layered transition metal oxide particles coated with boron / silicate still maintain a regular single crystal particle shape.

[0093] Figure 3 The figure shows the discharge curve of a coin cell made from the cathode material obtained in Example 1. As can be seen from the figure, the boron / silicate coated layered transition metal oxide has a higher first-cycle coulombic efficiency and reversible specific capacity than the uncoated sample.

[0094] Figure 4 The figure shows the cycle performance of the cathode material obtained in Example 1 when it is used to prepare a coin cell. As can be seen from the figure, the boron / silicate coated layered transition metal oxide has a higher capacity retention rate than the uncoated sample.

[0095] Figure 5 The NaNi prepared in Example 1 1 / 3 Fe 1 / 3 Mn 1 / 3 A schematic diagram of the core-shell structure of O2@NaFeSiO4. As can be seen from the diagram, the NaFeSiO4 coating layer serves as the shell structure, and the NaNi... 1 / 3 Fe 1 / 3 Mn 1 / 3 The structure is based on the O2 core.

[0096] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a sodium-ion cathode material, characterized in that, comprising: S1, uniformly mixing the metal compound with the boron-containing compound and the silicon-containing compound in the presence of a solvent to obtain solution A; The metal compound is selected from nitrates containing Mn and / or Co metal elements; the concentration of Mn ions and / or Co ions in the solution A is 0.025~0.04mol / L; the molar ratio of the metal compound to the total molar amount of the boron-containing compound and the silicon-containing compound is 0.5~2:1; the boron-containing compound is selected from at least one of boric acid, ammonium hydrogen borate and sodium borate; the silicon-containing compound is selected from at least one of orthosilicic acid, metasilicic acid and sodium silicate; wherein, the molar ratio of the boron-containing compound calculated as boron to the silicon-containing compound calculated as silicon is 1:1-1.5; S2, uniformly mixing the layered metal oxide with the solution A to obtain a mixed solution, and drying to obtain a mixed powder; Before the layered metal oxide is mixed with the solution A, it is calcined at 750~1100°C for 10~20h, so that the precursor fully reacts to obtain layered oxide particles with high crystallinity; the addition amount of the layered metal oxide makes the solid content in the mixed solution 11~16.5wt%; the drying conditions include: a drying temperature of 50~200°C and a drying time of 5~20h; after the boron-containing compound and the silicon-containing compound are hydrolyzed, a condensation reaction occurs with the surface of the layered metal oxide to form a chemical bond; S3. The mixed powder is subjected to heat treatment at a temperature of 600°C for 2 hours to obtain a sodium-ion cathode material of boron / silicate-coated layered metal oxide with a core-shell structure, the general formula being Na. m TMO2@Na x M y (SiO n ) z (BO3) 1-z ; TM is a 3d transition metal, M is selected from Mn and / or Co, wherein 0.5≤m≤1.2, 0<x<4, 0.5≤y<2, 0<z<1, 3≤n≤4; the layered metal oxide is in P2 and / or O3 phase; In the coating layer, the molar ratio of borate (calculated as boron) to silicate (calculated as silicon) is 1:1-1.5; the Young's modulus of the coating layer is 60-90 GPa, and the coefficient of thermal expansion of the boron / silicate coating layer is 3-20 × 10⁻⁶. -6 / K; In the sodium ion positive electrode material, the mass fraction of the coating layer composed of boron / silicate is 3.14~3.27%.

2. The preparation method according to claim 1, characterized in that, In step S1, the metal compound is selected from manganese nitrate tetrahydrate and / or cobalt nitrate hexahydrate.

3. The preparation method according to claim 1, characterized in that, In step S1, the boron-containing compound is selected from boric acid; the silicon-containing compound is selected from orthosilicic acid.

4. The preparation method according to claim 1, characterized in that, In step S1, the molar ratio of the metal compound to the total molar amount of the boron-containing compound and the silicon-containing compound is 0.8~1.2:

1.

5. The preparation method according to claim 1, characterized in that, The solvent is selected from water.

6. The preparation method according to claim 1, characterized in that, The 3d transition metal is selected from at least one of Mn, Fe, Co, Ni, Cu, Ti, Cr and V.

7. A sodium-ion cathode material, characterized in that, The cathode material is obtained by the preparation method according to any one of claims 1-6, wherein the cathode material is a boron / silicate-coated layered metal oxide with a core-shell structure and the general formula is Na. m TMO2@Na x M y (SiO n ) z (BO3) 1-z ; TM is a 3d transition metal, M is selected from Mn and / or Co, wherein 0.5≤m≤1.2, 0<x<4, 0.5≤y<2, 0<z<1, 3≤n≤4; In the coating layer, the molar ratio of borate radicals calculated as boron to silicate radicals calculated as silicon is 1:1-1.5; The Young's modulus of the coating layer is 60~90 GPa, and the coefficient of thermal expansion of the boron / silicate coating layer is 3~20×10⁻⁶. -6 / K.

8. The cathode material according to claim 7, characterized in that, The 3d transition metal is selected from at least one of Mn, Fe, Co, Ni, Cu, Ti, Cr and V; the layered metal oxide is in P2 and / or O3 phase; in the sodium ion positive electrode material, the mass fraction of the coating layer composed of boron / silicate is 3.14~3.27%.

9. A sodium-ion battery, characterized in that, comprising the sodium ion positive electrode material according to claim 7 or 8.

10. An application of the sodium ion battery according to claim 9 in the field of power transportation or energy storage.

Citation Information

Patent Citations

  • Nano magnesium lithium silicate coated high-nickel positive electrode material as well as preparation method thereof and application thereof

    CN111313024A

  • Modified layered oxide sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN117393736A

  • Olivine type lithium transition metal silicate compound, and method for manufacturing the same

    JP2015008102A

  • Cathode material of lithium ion secondary battery and method for manufacturing the same

    US20130011738A1

  • Cathode active material coated with f-doped lithium borosilicate and sulfide all-solid-state battery comprising same

    WO2025221493A1